Quasi-two-dimensional magnetism and antiferromagnetic ground state in Li2FeSiO4 - Hergett, Waldemar; Bouldi, N.; Jonak, M.; Neef, C.; Ritter, C.; Abdel-Hafiez, M.; Seewald, F.; Klauss, H.-H.; Haverkort, Maurits W.; Klingeler, Rüdiger (Physical review, 2025)
Our experimental (neutron diffraction, Mössbauer spectroscopy, magnetic susceptibility, specific heat) and numerical studies on the evolution of short- and long-range magnetic order in 𝛾II−Li2⁢FeSiO4 suggest a quasi-two-dimensional (2D) nature of magnetism. The experimental data obtained on single crystals imply long-range antiferromagnetic order below 𝑇N=17 K. A broad maximum in magnetic susceptibility 𝜒 at 𝑇m≃28 K, observation of magnetic entropy changes up to 100 K, and anisotropy in 𝜒 are indicative of low-dimensional magnetism and suggest short-range magnetic correlations up to 200 K. Neutron diffraction shows that long-range antiferromagnetic order is characterized by the propagation vector 𝐤=(12,0,12). The ordered moment 𝜇=2.50⁢(2) 𝜇B/Fe, at 𝑇=1.5 K, is along the crystallographic 𝑎 axis. This is consistent with the observed static hyperfine field of 𝐵hyp=14.8⁢(3)⁢T by Mössbauer spectroscopy which indicates significant orbital contributions. The temperature dependence of 𝐵hyp yields the critical exponent 𝛽=0.116⁢(12) which is in the regime of the 2D Ising behavior. LSDA+U studies exploiting the experimental spin structure suggest dominating magnetic exchange coupling within the 𝑎⁢𝑐 layers (i.e., 𝐽3≃−6 K and 𝐽6≃−2 K) while interlayer coupling is much smaller and partly frustrated. This confirms the 2D nature of magnetism and is in full agreement with the experimental findings.
Gesehen am 30.07.2025
Im Titel sind die Zahlen "2" und "4" tiefgestellt